Solar-Powered flood detection system using Arduino Uno - Mohd Syahnizam, Bin Garip (Universiti Malaysia Sarawak (UNIMAS), 2017)
Floods always occur unexpectedly and unpredictable. As today’s technologies is grow up, it helps everyday life of people becomes easier. This Flood Detector Warning System technology helps to monitor and give warning to people for facing the floods. By using one of the newest microcontroller technologies which is Arduino Uno R3, this system can be developed. Combining hardware and software, this system needed some programming part for interfacing. The water sensors are used to send the signal to microcontroller board for signal analysing into output. Applying the concept of wireless connection for communication, nRF24L01 + 2.4GHz wireless modem are used. Users can monitor flood far from the monitored area by displaying the output of water level on LCD (Liquid Crystal Display) and computer monitoring. This system is stable as it has a wireless transmitter and also can be connected by wire to the display. Building with presence of solar energy as backup power source, the energy for this system can be long lasting and more reliable compared to the conventional flood detection system. Other than that, this system is able to give warning to the user by producing alert system.